ICT in Education in Global Context The Best Practices in K-12 Schools - Zhang, Jinbao; Yang, Junfeng; Chang, Maiga; Chang, Tingwen (Lecture Notes in Educational Technology, 2016)
Intended to promote the innovative use of technology in education and promote educational advances all over the world, this volume brings together 16 best-practice cases on technology-enhanced educational innovations. Experts from Turkey, Tunisia, Cyprus, Italy, Malaysia, China, India and Finland have contributed to these cases, highlighting the current state-of-the-art in the use of technology in education in their respective counties. Topics include best practices for designing smart classrooms, effective use of tablets and interactive whiteboards, virtual learning environments, digital learning spaces, game-based learning, synchronous cyber classrooms, micro-courses, among others. The book offers an essential resource on emerging technologies and the educational approaches currently being pursued in different countries to foster effective learning.